Factors Affecting The Intention Of Whistleblowing Behavior - Yustiana Djaelani; Fitriani Sardju (STIEM BONGAYA, 2021)
The purpose of this study was to analyze the influence of attitudes, subjective norms, behavioral control and religiosity on the intentions of tax accounting students in carrying out whistleblowing actions. This research is a quantitative research. The respondents are tax accounting students. The sample in this study uses primary data. The data collected was processed using the SPSS version 2.1 program. The statistical method used to test the hypothesis is multiple linear regression analysis. The results of this research are subjective norms, behavioral control and religiosity affect the intention of tax accounting students in doing whistleblowing. And attitude has no effect on the intention of tax accounting students in doing whistleblowing.